The Challenges of Pre-Hospital Emergency Personnel in Sistan Area: A Qualitative Study - Mohammad Mohammadi; Mohammadreza Firouzkouhi; Abdolghani Abdollahimohammad; Maryam Shivanpour (Kerman University of Medical Sciences, 2019)
Introduction: Pre-hospital emergency (EMS) is actually a community-based system that responds to the needs of the injured or patients with emergency and acute illness, outside health care centers until they are transferred to a health facility. Therefore, this study aimed to explore the challenges that pre-hospital emergency personnel face with. Method: This qualitative study was conducted using thematic analysis. Using purposive sampling, 12 pre-hospital emergency personnel in Zabol were included in this study. Data were collected through semi-structured interviews. Braun and Clarke method was used to analyze the data. Results: The results extracted from the experiences of pre-hospital emergency personnel included four themes: emergencies as expectations of challenges, new challenges for old and new equipment, challenges of personnel conflict with needs and frequency of roles. Conclusion: According to the results, pre-hospital emergency personnel on mission work face with many problems. In order to improve the quality of services, pre-hospital emergency requires a reform of the organizational structure, reform of administrative rules and regulations, revision of educational programs, provision of the necessary facilities and equipment, employment of human resources needed, revision of the personnel monitoring and evaluation system, as well as providing welfare facilities for personnel.